Teacher training on Developing Deep Learning-Based Instructional Media for Senior High School and Islamic Senior High School in Batahan District - Resdilla Pratiwi; Desiana; Rona Adani Ulayya; Restina Liza (Yayasan Darussalam Bengkulu, 2026)
This Community Service Program (PKM) aims to strengthen the professional competence of Senior High School teachers in Batahan District by integrating Deep Learning technology into digital-based learning. The program responds to the demands of the Industrial Revolution 4.0 and Society 5.0, which require innovative, interactive, and adaptive teaching. However, limited training, weak digital infrastructure, and minimal technical guidance still hinder the use of digital media in schools. The program was carried out using a Participatory Action Research (PAR) approach with the Asset-Based Community Development (ABCD) model through discovering, mapping, connecting, and developing stages. Activities included intensive training, hands-on workshops, and mentoring in AI-based media development using ChatGPT, Gamma, Canva, and Quiziz. The results show increased teacher literacy in technology, creativity in pedagogy, and the ability to produce contextual AI-based digital media. This PKM contributes to developing innovative learning practices and is expected to encourage sustainable digital culture in Batahan schools.